Chromosome-level genome assembly of cultivated strawberry ‘Seolhyang’ (Fragaria × ananassa) - Hyeondae Han; Yoon Jeong Jang; Koeun Han; Han-Na Park; Do-Sun Kim; Seonghee Lee; Youngjae Oh (Scientific Data)
Abstract Cultivated strawberry (Fragaria × ananassa) belongs to the family Rosaceae and is an allo-octoploid species (2n = 8×  = 56). Using PacBio Revio long reads of ‘Seolhyang’, we completed telomere-to-telomere phased genome assemblies with a size of 797 Mb with a contig N50 of 27.04 Mb. Benchmarking of the universal single-copy orthologs (BUSCO) analysis detected 99.1% conserved genes in the assembly. In addition, the average long terminal repeat assembly index (LAI) was 17.28, with high genome continuity. In this study, we identified 50 of the possible 56 telomeres across 28 chromosomes. The ‘Seolhyang’ genome was annotated using RNA-Seq data representing various F. × ananassa tissues from the NCBI sequence read archive, which resulted in 129,184 genes.